STUDY OF PRODUCTION OF LIGHTWEIGHT CONCRETES BASED ON EXPANDED CLAY - Abdurahimov Abdukarim Abduhalimzoda (American Journals, 2023)
An important aspect of technical progress is the loss of mass in the use of effective material, in this case it is necessary to send porous fillers to them. The use of lightweight concrete reduces the mass of the building structure by 35%, and cement by 10%. In this situation, the size of the structure increases, and its thermotechnical and acoustic properties are improved. In the last 10 years, a lot of research and studies have been carried out on the selection of composition, stability of lightweight concrete in porous aggregates.
Keywords: Keramzit, light, concrete, chemical, additive, science, technology, the most important task is to increase the well-being of human life. That's why experts in every field deeply study how their field can serve the well-being of human life. Among these we can include construction materials engineers.